THE NORTHERN CAUCASUS: SPREAD OF JIHAD - DOBAEV, Igor (CENTRAL ASIA AND THE CAUCASUS, 2009)
The “post-perestroika” separatist-minded elites that came to power in Chechnia in the ear-ly 1990s and aspired to achieve ideological consolidation of the Chechens made an attempt to revive some of the elements of the old traditional social system based on blood kinship. At the grass-roots level there were clans of close blood relatives (from the bottom up: d’ozal, var, varis)and larger social structures (taips and tukhums)that together formed the Chechen nation—nokh-chi k’am. The great number of taips and tukhums and the fact that the Vainakhs lacked any state-hood experience buried the idea. The Chechen leaders had to place their stakes on the ideology of traditional “local Islam” of the Sufi virds Kun-ta-hajji and Vis-hajji that belonged to the Qadir-iyya Tariqah (known in Chechnia as Zikrizm). This did not create the desired ideological cohesion for the simple fact that the Chechens are scattered throughout several dozen Sufi structures (Vird brotherhoods). This moved “integration Islam,” which rejected everything that might di-vide the Muslims—races, ethnic groups, taips, and other local ethnic and confessional groups—to the frontline. In the Northern Caucasus it is known as Wahhabism (Salafism). Today, with part of the road toward restored normalcy in Chechnia successfully covered, the situation still leaves much to be desired. The de-feat of the separatists in Chechnia and the spread of the Salafi ideology across the Northern Cau-casus transformed “resistance” partly into “guerrilla warfare” and partly into mobile and loosely connected terrorist groups.